A BATHYMETRY-BASED RESERVOIR SEDIMENTATION EVALUATION (Malaysian Journal of Civil Engineering, 2018)
Reservoir sedimentation is a serious problem that normally reduces the capacity of a dam (reservoir) for water storage over a given period of time. This can lead to insufficient availability of water for domestic uses, irrigation and hydropower. This study was conducted to determine the rate of sedimentation, sediment yield and the capacity of the University of Ilorin dam (Ilorin, Nigeria) between June 2007 and June 2014. Geographic Information System (GIS), Global Positioning System (GPS), canoe and lead-line techniques were used for the measurement of depth of the reservoir of the dam. Soil and Water Assessment Tool (SWAT) model was used to simulate the sediment yield. The initial capacity of the dam after construction in 2007 was 1.800 x 106 m3 but this capacity was reduced to 1.411 x 106 m3 in 2014 due to sedimentation. The sediment was found to be clay soil which covered 389,170 m3 of the reservoir and the mean bulk density of the clay soil sediment was 1139 kg/m3. The mean values of clay, silt and sand contents of the sediment yield were 46.5, 35.6 and 17.9 %, respectively. The annual sediment yield was high in the reservoir due to farming activities at the upstream end of the dam, annual rate of sedimentation was 12.78 m3/ha/yr and sediment yield was 14,557.14 kg/ha/yr. Farming activities should be prevented at the upstream of the dam and dredging should be done every 10 years when 30.87% of the storage capacity would be occupied by sediment.